Implementasi Kebijakan Pendidikan Anti Korupsi di Sekolah Dasar - Husna, Nurul; Hermina, Dina (Interdisciplinary Explorations in Research Journal, 2024)
Corruption is one of the main obstacles in development that harms not only economically, but also erodes the moral values of society. Anti-corruption education at the primary school level has an important role in shaping the character of the younger generation who uphold the values of honesty, integrity and responsibility. This research aims to analyze the implementation of anti-corruption education policies in primary schools through a literature study approach. Policies such as Law No. 19/2019 on KPK, South Kalimantan Governor Regulation No. 069/2020, and Banjarbaru Mayor Regulation No. 10/2020 are the main basis for the integration of anti-corruption education into the curriculum. The results show that strategic measures such as integrating anti-corruption materials in subjects, using interactive teaching methods, and cooperation between teachers and parents are effective in instilling anti-corruption values in students. Creative approaches, such as educational games, inspirational stories, and extracurricular activities, are able to motivate students to understand the adverse effects of corruption and foster ethical commitment. With well-planned and collaborative anti-corruption education, it is hoped that a generation with high integrity, able to fight corruption, and contribute to a just and transparent society will be formed.